Sebaran Daerah Asal Pengunjung Virtual Tour Museum Nasional menggunakan Analisis Tetangga Terdekat - Putri Haviarini, Cynthia; Hotimah, Oot; Sya, Ahman (Jurnal Spatial Wahana Komunikasi dan Informasi Geografi, 2022)
This research is useful for knowing the origin of visitors who visit the Museum Nasional through a virtual tour of the Museum Nasional. This is because virtual tours are a new breakthrough for tourism activities in Indonesia. The method used is a survey approach with a sampling technique in the form of accidental sampling through google forms distributed through social media, such as twitter, WhatsApp group, comments on the Museum Nasional YouTube channel, and Instagram starting on December 26, 2021 - January 6, 2022, namely as many as 42 people and the number of respondents obtained on July 25 – July 30, 2022, as many as 62 people with a total of 104 respondents who made virtual visits to the Museum Nasional. Results Based on what was obtained, most of the visitors came from the provinces of DKI Jakarta, West Java, Central Java, Banten, and East Java. To determine visitors who do virtual tours of the Museum Nasional, researchers use Nearest Neighbor Analysis contained in the ArcGIS application. In this case, the researchers digitized the distribution points of visitors (by district/city) who made virtual visits to the Museum Nasional which got 27 points from the districts/cities of origin of visitors (104 research respondents). Then, the results of the distribution category are dispersed distributed because the Nearest Neighbor Ratio is 32,094.